2017
DOI: 10.1055/s-0043-103956
|View full text |Cite
|
Sign up to set email alerts
|

Early adverse events and long-term outcomes of endoscopic sphincterotomy in a pediatric population: a single-center experience

Abstract: The use of endoscopic sphincterotomy (EST) in the management of pancreaticobiliary disease in children is increasing. However, studies of long-term outcomes are limited in pediatric patients. Therefore, this study evaluated the early adverse events and long-term outcomes following EST in pediatric patients. We retrospectively analyzed data from 198 pediatric patients who underwent ESTs at Asan Medical Center Children's Hospital between 1994 and 2013. The median age was 8.7 years (range 18 months to17 years). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 34 publications
0
16
0
1
Order By: Relevance
“…Систематический анализ, проведенный Cho JM и соавт., показал, что общая частота осложнений эндоскопического лечения составляет 6% (95% доверительный интервал 4-8%), включая постэргический панкреатит (4,7%), кровотечение (0,6%) и инфекции (0.8%) [45].Факторы риска развития постэргического панкреатита у детей включают: инъекцию контраста в панкреатический проток и панкреатическую сфинктеротомию.…”
Section: методы исследованияunclassified
“…Систематический анализ, проведенный Cho JM и соавт., показал, что общая частота осложнений эндоскопического лечения составляет 6% (95% доверительный интервал 4-8%), включая постэргический панкреатит (4,7%), кровотечение (0,6%) и инфекции (0.8%) [45].Факторы риска развития постэргического панкреатита у детей включают: инъекцию контраста в панкреатический проток и панкреатическую сфинктеротомию.…”
Section: методы исследованияunclassified
“…The safety of ERCP has been evaluated in several recent studies [ 10 , 16 , 17 ]. A recent systematic review and meta-analysis has shown a pooled complication rate of 6% (95% confidence interval 4%–8%) including post-ERCP pancreatitis (4.7%), bleeding (0.6%), and infections (0.8%) [ 17 ].…”
Section: Endoscopic Retrograde Cholangiopancreatography In Childrenmentioning
confidence: 99%
“…The risk factors for post-ERCP pancreatitis in children include injection of contrast into the pancreatic duct and pancreatic sphincterotomy [ 18 ]. Cho et al, analyzed the adverse events and long-term outcomes associated with an endoscopic sphincterotomy in a pediatric population [ 16 ]. In this retrospective study, early adverse events (<30 days) included pancreatitis (5.7%), bleeding (2.0%), sepsis (1.0%), and perforations (0.7%).…”
Section: Endoscopic Retrograde Cholangiopancreatography In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies on ERCP in children are retrospective in design and involve small numbers, mainly because of the overall small proportion of procedures compared to those in adult populations. In this issue of Endoscopy, Cho et al have tried to fill in some of the gaps, by evaluating the early adverse events and long-term outcomes following 294 endoscopic sphincterotomies in 198 children with pancreaticobiliary diseases [5]. This retrospective single-center study from Korea has a follow-up duration of median 3.5 years with a wide range (2 -232 months).…”
mentioning
confidence: 99%